A hemicellulose and lignin-first process for corn stover valorization catalyzed by aluminum sulfate in γ-butyrolactone/water co-solvent. Issue 19 (9th August 2022) - Luo, Yiping; Wei, Min; Jiang, Bin; Zhang, Mingyi; Miao, Qian; Fu, Hongquan; Clark, James H.; Fan, Jiajun
Abstract : A hemicellulose and lignin-first process for corn stover valorization with unique roles of Al2 (SO4 )3 in GBL/H2 O. Abstract : A novel hemicellulose and lignin-first process for corn stover valorization catalyzed by Al2 (SO4 )3 in GBL/H2 O co-solvent was developed in this study. In 25% GBL/H2 O at 160 °C, Al2 (SO4 )3 assisted H2 O in breaking down intermolecular linkages of corn stover. The hydrolysis of Al2 (SO4 )3 could produce H +, [Al(OH)2 (H2 O) x ] + and SO4 2− . With the solvation of GBL, the H + and [Al(OH)2 (H2 O) x ] + from Al2 (SO4 )3 hydrolysis increased the co-conversion and dissolution of hemicellulose (96.9 wt%) and lignin (68.0 wt%), while the AlHSO4 (OH)2 H2 O species formed by combining with [Al(OH)2 (H2 O) x ] + and SO4 2− was found to inhibit cellulose conversion (88.7 wt% kept). Expecting for H + from Al2 (SO4 )3 hydrolysis, the formed AlHSO4 (OH)2 H2 O was found to be the catalytic active species for the cleavage of glycosidic bonds in hemicellulose to produce xylose, and also acted as a "stabilizer" to prevent the further degradation of xylose to improve its yield (87.6%, based on the weight of hemicellulose). Al2 (SO4 )3 selectively promoted lignin depolymerization to lower M w oligomers, as well as monophenols (11.20%) with high selectivity of 70.0% to VG and VP via Cα –OH dehydration and –Cγ (O)–OH decarboxylation reaction. The obtained cellulose-rich residues show great potential for further use within many industrial processes. The developed process is recyclable, giving important insights to design new approaches for corn stover valorization.